Portfolios of Agile Projects: A Complex Adaptive Systems’ Agent Perspective - and Sweetman, Roger; Conboy, Kieran (Project Management Journal, 2018)
While agile approaches can be extremely effective at a project level, they can impose significant complexity and a need for adaptiveness at the project portfolio level. While this has proven to be highly problematic, there is little research on how to manage a set of agile projects at the project portfolio level. What limited research that does exist often assumes that portfolio-level agility can be achieved by simply scaling project level agile approaches such as Scrum. This study uses a complex adaptive systems lens, focusing specifically on the properties of projects as agents in a complex adaptive portfolio to critically appraise current thinking on portfolio management in an agile context. We then draw on a set of 30 expert interviews to develop 16 complex adaptive systems (CAS)-based propositions as to how portfolios of agile projects can be managed effectively. We also outline an agenda for future research and discuss the differences between a CAS-based approach to portfolio management and traditional approaches.